Oral pharmacokinetics of a pharmaceutical preparation of florfenicol in broiler chickens - Gutierrez, Lilia; Guzman-Flores, Aline; Monroy-Barreto, Minerva; Ocampo, Luis; Sumano, Hector (Frontiers in Veterinary Science, 2023)
The use of florfenicol must follow particular pharmacokinetic/pharmacodynamic (PK/PD) ratios, i.e., it requires achieving serum concentrations at or slightly above the pathogen's minimum inhibitory concentration (MIC) during the dosing interval and that the ratio of area under the concentration vs. time curve (AUC)/MIC be as high as possible (still undetermined for poultry). As an alternative to the standard soluble florfenicol that is administered to the flock through drinking water, florfenicol premix is often recommended as feed medication in Latin America. However, no particular pharmaceutical design has been proposed. This study compared the PK of two preparations of florfenicol in broiler chickens and pondered the possibility of each covering the referred PK-PD ratios as predictors of clinical efficacy. The preparations were: a pharmaceutical form as FOLA pellets (F=bioavailability; O=optimum; LA=long-acting) and the premix formulation. The former are small colored pellets with vehicles and absorption enhancers of florfenicol designed for long action, and the latter was the reference premix of the antibiotic. First, these two pharmaceutical forms of florfenicol were administered as oral boluses (30 mg/kg), aided by a probe. In a second trial of the dosing form, both pharmaceutical preparations of florfenicol were administered in feed and ad libitum (110 ppm; approximately 30 mg/kg). In both cases, FOLA-florfenicol presented much higher relative bioavailability (3.27 times higher) and mean better residence time than florfenicol-premix (twice as high when forced as bolus dose). Consequently, FOLA-florfenicol possesses better PK/PD ratios vs. less sensitive pathogens, i.e., E. coli. It is proposed that if a metaphylactic treatment of a bacterial outbreak in poultry is implemented with florfenicol prepared as FOLA, better PK/PD ratios will be obtained than those of standard florfenicol premix. Clinicians must confirm that feed consumption in the flock has not been affected by the particular disease if FOLA pellets of florfenicol are used.